TREATMENT TACTICS FOR RECTOVAGINAL FISTULAS - Аlimova Zulayho Quvondiqovna; Sherbekov Ulugbek Akhrorovich (Western European Studies, 2024)
Rectovaginal fistulas are a challenging and unresolved issue in the fields of colorectal surgery, pelvic surgery, gynecology, and urology. Numerous surgical methods have been proposed to treat rectovaginal fistulas. However, the rate of disease recurrence and postoperative complications remains high. This is largely due to the lack of an individualized approach in determining the surgical method for treating rectovaginal fistulas, necessitating the exploration of new surgical technologies and the development of treatment algorithms.
Keywords: Rectal fistulas; flesh; coloproctology